Relationship of endothelial dysfunction with degree of renal function damage and lipidemic profile in patients with type 2 diabetes mellitus and hypertension. - Pertseva, N. O. (Medicni Perspektivi, 2014)
In the article defining relationship between endothelial dysfunction, the degree of renal and lipidemic profile damage in 234 patients with type 2 diabetes mellitus with hypertension was carried depending on the quality of glycemic control. It is shown that the deepening of endothelial dysfunction in patients with insufficient and poor compensation tightly correlates with the degree of renal and lipidemic disorders. In these patients there was a significant increase in the level of albuminuria, reduction in glomerular filtration rate, increase of concentrations of urea and creatinine. Against the background of poor hyperglycemia, compensation total cholesterol, low density lipoprotein content increases by 73,3% (p<0.05), hypertriglyceridemia twice exceeds the control values. In patients with type 2 diabetes mellitus with poor compensation the most significant correlation links were observed between the concentration of endothelin-1 and the level of microalbuminuria (r=+0,79), as well as the content of low density lipoprotein cholesterol (r=+0.81). Thrombomodulin concentration is in direct correlation with microalbuminuria (r=+0.76), hypercholesterolemia (r=+0.80) and hypertriglyceridemia (r=+0.83), indicating to increasing interaction between the pathogenetic mechanisms which cause depression of endothelial dysfunction, renal and dyslipidemic disorders with increasing hyperglycemia.